The Influence of Financial Literacy, Financial Inclusion and Financial Technology on the Financial Performance of M-SMEs in Pekalongan City - Masrochah Maela; Notoatmojo M. Iqbal (SHS Web of Conferences, 2025)
Examining how financial performance is affected by financial technology, financial inclusion, and financial literacy on the financial performance of M-SMEs in Pekalongan City is the goal of this study. Using the basic random selection technique, 100 respondents were chosen as samples for this investigation. MSME actors in Pekalongan City were given questionnaires to complete in order to collect data, which was then analyzed using SPSS Statistics 25.0. The examination of data approach used in this study is multiple linear regression testing. The study’s findings largely indicate that while financial technology has little bearing on M-SMEs’ financial success, financial literacy and financial inclusion do. Financial technology, financial inclusion, and financial literacy all simultaneously impact M-SMEs’ financial success.